Menghai Huangye, a novel albino tea germplasm with high theanine content and a high catechin index. (October 2021) - Pang, Dandan; Liu, Yufei; Sun, Yunnan; Tian, Yiping; Chen, Linbo
Highlights: We identified an albino tea plant with high theanine from Yunnan Province—'Menghai Huangye' (MHHY). MHHY was different from conventional tea plants in that it had a high catechin index. The high catechin index was closely correlated with the balance of transcription amounts between F 3′ H and F 3′5′ Ha in MHHY. The 284 bp deletion of the CsF 3′ H promoter in MHHY might lead to its low expression. Abstract: Yunnan Province has a very wide diversity of tea germplasm resources. A variety of special tea germplasms with outstanding traits have been discovered, including tea germplasms with high anthocyanin content and low caffeine content. Albino tea cultivars generally have higher contents of theanine that contribute to the umami taste, and the quality of tea brewed from it is higher. The catechin index (CI), the ratio of dihydroxylated catechins (DIC) to trihydroxylated catechins (TRIC), is a crucial index of suitability for processing tea. In this study, the albino tea plant Menghai Huangye (MHHY) with yellow leaves was identified. Analysis of the biochemical components revealed that MHHY was enriched in theanine and the total catechins (TC) were lower than Yunkang 10 (YK10). In addition, the CI value of MHHY was extremely significantly higher than that of YK10. Metabolic profile of catechins and the related gene expression profile analysis found that the coordinated expression of the key branch genes F 3′ H and F 3′5′ Ha for the synthesis of DIC and TRIC in tea plant was closely related to the high CI and low TC of MHHY. Further analysis of the F 3′ H promoter showed that a 284-bp deletion mutation was present in the F 3′ H promoter of MHHY, containing the binding sites of the transcriptional repressor MYB4 involved in flavonoid metabolism, which might be an important reason for the up-regulated expression of F 3′ H in MHHY. Overall, this study provides a theoretical basis for understanding the characteristics of albino tea germplasm resources and efficiently utilizing high-CI tea germplasm resources.